SELEKSI ISOLAT BAKTERI ASAM LAKTAT ASAL TEMPE DAN TAPE SEBAGAI KANDIDAT PROBIOTIK - Raini Panjaitan; Lilis Nuraida; Ratih Dewanti-Hariyadi (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2018)
Lactic acid bacteria (LAB) have been isolated from Indonesian fermented foods such as tempe and tape. Some lactic acid bacteria are known to have health benefits and as probiotics. The objective of this study was to evaluate the probiotic potential of lactic acid bacteria isolated from tempe and tape. LAB isolated from tape were evaluated for their tolerance towards low pH (pH 2.0) and 0.5% bile salt. LAB isolated from tape and tempe resistant to low pH and bile salt were then evaluated for their antimicrobial activities against pathogenic bacteria (E. coli ATCC 25922, S. typhimurium ATCC 14028, L. monocytoge-nes ATCC 7644, S. aureus ATCC 25923 and B. cereus ATCC 11778). The isolates were also tested for their adherence properties, consisting of hidrophobicity test using microbial adhesion to solvents (MATS) assay, autoaggregation as well as coaggregation between LAB and pathogens. The results of this study indicated that three isolates from tape (L. fermentum 1 BK2-5, L. fermentum 2 BK2-7, P. acidilactici NG6-4) showed good tolerance to pH 2.0 and 0.5% bile salt. L. fermentum S21209 isolated from tempe showed the strongest antimicrobial activity against the five pathogens tested. Based on the adhesion to xylene, L. fermentum 1 BK 2-5 was categorized as strong hydrophobic, followed by L. fermentum S21209 and L. fermentum TS4-5. Meanwhile, L. fermentum TS 4-5, L. fermentum S21209, L. fermentum 1 BK 2-5 and P. pentose-ceus 1 W2SR04 have the highest autoaggregation ability. L. fermentum S21209 also had the highest co-aggregation ability to the five pathogenic bacteria tested. The ability of LAB to coaggregate with all pathogens tested correlated with their strong antimicrobial properties. Based on the resistance toward low pH and bile salt, antimicrobial activity and adherence properties, L. fermentum S21209 from tempe and L. fermentum 1 BK 2-5 from tape are the most potential as probiotic candidates.